THE DEVELOPMENT AND IMPORTANCE OF THE BRAZILIAN AERONAUTICAL INDUSTRY - Araujo Junior, Antonio Henriques de; Viagi, Arcione Ferreira (Revista Ciências Exatas, 2025)
The Brazilian aeronautical industry has emerged as a global leader, combining technological advancements, economic contributions, and strategic development. Rooted in mid-20th-century initiatives with the establishment of key institutions like the Instituto Tecnológico de Aeronáutica (ITA) and the Centro Técnico Aeroespacial (CTA), the sector saw a significant leap with the founding of Embraer in 1969. This paper explores the historical context, the role of educational institutions, technological progress, and economic impacts. We analyze how innovation, partnerships, and sustainability challenges have shaped the industry's modern success and global competitiveness. Through a qualitative methodology, this study integrates historical analysis, economic assessment, and technological evaluations, drawing on academic articles, industry reports, and government data.